Analysis of Specific IgG Titers Against Tick-Borne Encephalitis in Patients with Primary Antibody Deficiency Under Immunoglobulin Substitution Therapy: Impact of Plasma Donor Origin - Goldacker, Sigune; Witte, Torsten; Huzly, Daniela; Schlesier, Michael; Peter, Hans-Hartmut; Warnatz, Klaus (Frontiers in Immunology, 2015)
Immunoglobulin (Ig) replacement therapy is effective in reducing infections in patients with primary antibody deficiency (PAD). Diversity of specific antibodies is achieved by pooling plasma from over 1000 donors usually of a given geographic region. However, there is no agreement with regard to an optimal vaccination schedule for plasma donors. Especially for tick-borne encephalitis (TBE) regional vaccination rates differ widely among populations due to the epidemiology of the disease. We analysed specific antibody titres against TBE in comparison to total IgG levels in 162 serum samples collected from 110 PAD patients substituted with polyvalent intravenous (IVIG) or subcutaneous (SCIG) IgG. Some patients received different IgG products over time leading to a total number of 122 different patient-IgG product combinations. Positive TBE-specific IgG levels were detected in 35 cases when measured by standard ELISA and could be confirmed by demonstration of neutralizing antibodies in 31 cases. The detection of specific antibody levels correlated with the geographic origin of the IgG preparations. No titres were detectable in patients substituted with IgG products from North American donors, whereas variable degrees of anti-TBE titres were observed in patients receiving products from different European countries. We suggest considering the patients’ personal risk for TBE when selecting an appropriate Ig preparation. These data support regional plasma donation in order to address the diverse local infection profile.